Uterine Fibroids A Clinical Casebook (Springer International Publishing, 2018)
Comprised of clinical cases presenting diverse clinical scenarios of uterine fibroids, this concise, practical casebook will provide clinicians in reproductive medicine and obstetrics/gynecology with the best real-world strategies to properly diagnose and treat the various presentations of fibroids they may encounter in daily clinical practice. Opening with chapters discussing classification and pathogenesis, effects on fertility and treatment modalities for these common tumors, each subsequent chapter is a case that provides a unique clinical presentation of a patient's symptoms and clinical findings, diagnostic work-up and the thought process involved in navigating the treatment options as well as the supporting evidence. Cases included illustrate different types and locations of fibroids in addition to various management strategies, complications and outcomes, and selected chapters also include video clips. Pragmatic and reader-friendly, Uterine Fibroids: A Clinical Casebook is written by experts in the field and is designed to facilitate and guide reproductive medicine specialists and gynecologists in the sometimes challenging decision-making process by presenting real case scenarios that span the spectrum of fibroid presentations and treatment options.